The current evidence-based management of distal radial fractures: UK perspectives. (June 2019) - Johnson, Nick A.; Dias, Joseph
Distal radial fractures are extremely common injuries, yet many basic questions remain unanswered about their optimum management. Recently in the United Kingdom several guideline development groups have produced national standards and best-practice guidelines based on review of the best available evidence and expert knowledge. All guideline groups agree that when surgery is needed for dorsally displaced distal radial fractures, that can be reduced closed, K-wire fixation and cast immobilization, should be offered. Further research questions have been identified. The important findings and recommendations are summarized in this article.